Regulation and functional importance of human periodontal ligament mesenchymal stromal cells with various rates of CD146+ cells - Miłek, Oliwia; Schwarz, Katharina; Miletić, Alma; Reisinger, Johanna; Kovar, Alexander; Behm, Christian; Andrukhov, Oleh (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMesenchymal stromal cells (MSCs) with high expression of CD146 have superior properties for tissue regeneration. However, high variability in the rate of CD146+ cells among donors is observed. In this study, the possible reasons behind this variability in human periodontal ligament MSCs (hPDL-MSCs) were explored.MethodshPDL-MSCs were isolated from 22 different donors, and rates of CD146+ cells were analyzed by flow cytometry. Furthermore, populations with various rates of CD146+ cells were isolated with magnetic separation. The dependency of cell proliferation, viability, cell cycle, and osteogenic differentiation on the rates of CD146+ cells was investigated. Besides, the effects of various factors, like cell density, confluence, and inflammatory environment on the CD146+ rate and expression were analyzed.ResultsThe rate of CD146+ cells exhibited high variability between donors, with the percentage of CD146+ cells ranging from 3% to 67%. Higher percentage of CD146+ cells was associated with higher proliferation, presumably due to the higher percentage of cells in the S-phase, and higher osteogenic differentiation potential. Prolonged cell confluence and higher cell seeding density led to the decline in the rate of CD146+ cells. The surface rate of CD146 in hPDL-MSCs was stimulated by the treatment with interleukin-1β and tumor necrosis factor-α, and inhibited by the treatment with interferon-γ.ConclusionThese results suggest that hPDL-MSCs with high rate of CD146+ cells are a promising subpopulation for enhancing the effectiveness of MSC-based regenerative therapies, however the rate of CD146 is affected by various factors, which must be considered for cell propagation and their potential application in vivo.